Characteristic Comparison of CHD for Active Smoker by Smoking Characteristic - Desy Diastutik (Universitas Airlangga, 2016)
Coronary Heart Disease (CHD) is a cardiovascular disease that has the highest morbidity and mortality rates in the non-communicable disease group both in the world and in Indonesia. One of the factors that influence the incidence of coronary heart disease is smoking behavior. The aim of the study was to analyze the proportion of characteristics of patients with coronary heart disease in active smokers based on smoking characteristics. This study was an observational study with cross-sectional study design. This research was conducted at the Cardiology Poly Regional Public Hospital (RSUD) Sidoarjo in May 2016. A total of 38 active smokers were used as research samples who were patients at the Heart Poly Hospital of Sidoarjo. Sampling using an accidental sampling technique. The variables studied were the respondent's characteristics, namely age, sex, last education, and work status, and the smoking characteristics variable, namely the long history of smoking, the type of cigarette, the number of cigarettes per day, and when smoking). Data analysis using epi info software and presented descriptively. The results showed that the majority of both respondents who suffered from coronary heart disease and non-coronary heart disease had a history of smoking for ≥ 33 years, smoking cigarettes less than 13 cigarettes/day, and not smoking immediately after waking up in the morning. The conclusion of the study was the highest proportion of the characteristics of coronary heart disease events in active smokers was cigarette type while the lowest was a long history of smoking.